Reviewing Leadership : A christina evaluation of current approaches - Bank, Robert (Engaging Culture (Cultura atractiva), 2004)
This book offers an acute theological analysis of the influence and importance of leadership in our culture today. The authors begin by analyzing the current growing interest in leadership and examining its development within the church. Next, they consider the spiritual dimensions of leadership. Finally, they offer examples of exceptional Christian leadership and discuss ways to nurture this type of leadership for the future.